2017
DOI: 10.1088/1748-605x/aa7b55
|View full text |Cite
|
Sign up to set email alerts
|

Development of fish collagen/bioactive glass/chitosan composite nanofibers as a GTR/GBR membrane for inducing periodontal tissue regeneration

Abstract: The development of a guided tissue or bone regeneration (GTR/GBR) membrane with excellent performance has been a major challenge in the biomedical field. The present study was designed to prepare a biomimetic electrospun fish collagen/bioactive glass/chitosan (Col/BG/CS) composite nanofiber membrane and determine its structure, mechanical property, antibacterial activity, and biological effects on human periodontal ligament cells (HPDLCs). The effects of this composite membrane on inducing periodontal tissue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…Thus, BG content was increased as much as we could, whereas electrospinning was possible. Consequently, mechanical properties of the membranes were in the acceptable range for GBR applications, because the UTS values of similar GBR membranes were reported to be in between 1 and 20 MPa (Requicha et al, 2016;Zhou et al, 2017).…”
Section: Alizarin Red Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, BG content was increased as much as we could, whereas electrospinning was possible. Consequently, mechanical properties of the membranes were in the acceptable range for GBR applications, because the UTS values of similar GBR membranes were reported to be in between 1 and 20 MPa (Requicha et al, 2016;Zhou et al, 2017).…”
Section: Alizarin Red Stainingmentioning
confidence: 99%
“…As cell source for GBR applications, adult stem cells have been widely preferred because of their favourable interaction with organic or inorganic biomaterials (Mota et al, 2012;Requicha et al, 2016;Sheikh et al, 2017;Türkkan et al, 2017;Zhou et al, 2017).…”
mentioning
confidence: 99%
“…It was reported that chitosan acted synergistically with chlorhexidine or minocycline in collagen membranes for periapical GTR, (J. Wang et al 2016; Kaya et al 2014) showing antibacterial properties as well as biocompatibility and barrier function against Enterococcus faecalis ). On the other hand, chitosan has been widely employed for GBR membranes blended with other natural polymers such as collagen, against S. mutans [42], and PCL and gelatin, against Escherichia coli and Staphylococcus aureus (Figure 1) [37]. As an alternative, Jin et al recently studied a composite-membrane combining chitosan and silver particles, which they hypothesized it could release silver ions from the fibers in a controlled manner in order to achieve enough antibacterial effects without affecting the biocompatibility of the material [30,30,43].…”
Section: Membranes For Guided Tissue/bone Regenerationmentioning
confidence: 99%
“…Polycaprolactone (PCL) membranes synthesized using the electrospinning technique can be loaded with anti-inflammatory drugs (such as ibuprofen) and growth factors (such as bone morphogenetic protein-2 (BMP-2)) to enhance periodontal regeneration [25]. Biomimetic fish collagen/ bioactive glass/ chitosan composite nanofiber membranes (Col/BG/CS) have good hydrophilicity, higher porosity and surface area promoting cell-cell and cell-matrix interaction, adequate tensile strength, and limited antibacterial properties [26]. Clinically available collagen membranes may be functionalized by electrospinning poly-DL-lactic acid (PDLLA) polymers to enhance periodontal regeneration.…”
Section: Membranes For Periodontal Tissue Regenerationmentioning
confidence: 99%